A state-of-the-art review of N self-doped biochar development in supercapacitor applications - Xiaorui, Liu; Haiping, Yang (Frontiers in Energy Research, 2023)
Due to the renewability, eco-friendly and cost-effective, biochar is considered to be a promising alternative to fossil fuel-based carbon for electrodes materials application in supercapacitors. However, the pristine biochar often exhibits poor structure and low activity which strongly inhibit its commercial utilization. N-doping is an efficient way to improve the electrochemical performance of biochar by enhancing the conductivity and surface wettability which then further induce pseudo-capacitance effect. Compared with external doping, synthesis of N self-doped biochar from natural N-rich biomass without utilization of external N precursors which are harmful and costly has attracted increasing attention. Few reviews with respect to N-doped biochar application in supercapacitor are available while that of N self-doped biochar is still scarce. This paper reviewed the latest developments in recent 10 years on the preparation, activation and application of N self-doped biochar in supercapacitors. Notably, the evolution of N-functionalities during N self-doped biochar production with or without activating agents was analyzed. The relationships between N content and the specific capacitance as well as the contribution of N self-doping induced pseudo-capacitance to the total specific capacitance were also discussed. Finally, the challenges and the prospects of N self-doped biochar application in supercapacitor were proposed.